2020
DOI: 10.1007/s12350-019-01958-8
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality imaging: Bird’s eye view from the European Society of Cardiology Congress 2019 Paris, August 31st–September 4th, 2019

Abstract: At the European Society of Cardiology (ESC) congress of this year 2019, held in Paris from August 31st to September 4th, 4509 abstracts were presented. Of those, 414 (9%) belonged to an imaging category. Experts in echocardiography (VD), nuclear imaging (AS), cardiac computed tomography (CT) (MD) and cardiovascular magnetic resonance (CMR) (CBD), have selected the abstracts in their areas of expertise that were of most interest to them and are summarized in this bird's eye view from this ESC meeting. These abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…1,2 Notably, 18 F-NaF uptake provides incremental prognostic information beyond that provided by macrocalcifications alone. [2][3][4][5] For example, higher 18 F-NaF uptake predicts progression of calcific aortic stenosis, development of restenosis following peripheral arterial interventions, and future myocardial infarctions (MIs), independent of CAC. [6][7][8] Along the same lines, thoracic aortic 18 F-NaF uptake has been shown to associate with established clinical cardiovascular risk scores.…”
mentioning
confidence: 99%
“…1,2 Notably, 18 F-NaF uptake provides incremental prognostic information beyond that provided by macrocalcifications alone. [2][3][4][5] For example, higher 18 F-NaF uptake predicts progression of calcific aortic stenosis, development of restenosis following peripheral arterial interventions, and future myocardial infarctions (MIs), independent of CAC. [6][7][8] Along the same lines, thoracic aortic 18 F-NaF uptake has been shown to associate with established clinical cardiovascular risk scores.…”
mentioning
confidence: 99%
“…8,9 Furthermore, it has been shown to predict subsequent macrocalcification as well as progression of coronary artery calcification (CAC) scores. 10 Moreover, 18 F-NaF uptake is increased in culprit coronary and carotid plaques in the setting of adverse CV events, predicts restenosis following endovascular intervention for peripheral arterial disease, and predicts progression of aortic stenosis. [3][4][5][6] In a recent study, coronary 18 F-NaF uptake was shown to independently predict future myocardial infarctions in individuals with stable CAD beyond standard risk assessment modalities including CAD risk scores, CAC, as well as angiographic burden and severity of CAD.…”
mentioning
confidence: 99%